2001
DOI: 10.1007/pl00001832
|View full text |Cite
|
Sign up to set email alerts
|

Variability in herbivore-induced odour emissions among maize cultivars and their wild ancestors (teosinte)

Abstract: Summary. Maize plants respond to caterpillar feeding with the release of relatively large amounts of specific volatiles, which are known to serve as cues for parasitoids to locate their host. Little is known about the genetic variability in such herbivore-induced plant signals and about how the emissions in cultivated plants compare to those of their wild relatives. For this reason we compared the total quantity and the qualitative composition of the odour blend among eleven maize cultivars and five wild Zea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
2
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 30 publications
3
156
2
2
Order By: Relevance
“…emissions among different maize lines (Gouinguene´et al, 2001;Fritzsche-Hoballah et al, 2002;Degen et al, 2004). Variability among maize lines is tremendous and it can be concluded that both maize lines tested here produce a volatile blend that falls well within the common range.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…emissions among different maize lines (Gouinguene´et al, 2001;Fritzsche-Hoballah et al, 2002;Degen et al, 2004). Variability among maize lines is tremendous and it can be concluded that both maize lines tested here produce a volatile blend that falls well within the common range.…”
Section: Discussionmentioning
confidence: 65%
“…These same compounds are commonly released by many other maize varieties in response to caterpillar feeding (Figure 1; Gouinguene´et al, 2001;Fritzsche-Hoballah et al, 2002;Degen et al, 2004). The ratios among the compounds are also common and did not differ between the isogenic and transgenic line.…”
Section: Odour Emissionsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, genotype specific differences in volatile emissions from undamaged plants have been found in potato (Wang and Kays 2002), rice (Rapusas et al 1996), cotton (Elzen et al 1986) and pear (Scutareanu et al 2003). A high genetic variability in volatile emissions from herbivore-damaged plants has also been shown in cotton (Loughrin et al 1995) and maize (Degen et al 2004;Gouinguené et al 2001). In other plant-herbivore systems, various organic compounds produced in response to plant damage have been shown to affect plant defence and plant gene expression in neighbouring plants, deterring herbivores and attracting their natural enemies (Dicke et al 2003;Baldwin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These are emitted upon damage by the host and are both reliable and detectable. In natural ecosystems, host-parasitoid interactions take place in habitats composed of several to many plant species, where both the expectancy of the host's presence and the specificity of volatile infochemicals may show great between-and within-plant variation (Takabayashi et al, 1994;De Moraes et al, 1998;Vet, 1999;Gouinguené, 2001). Variation in odors among plant species and cultivars can be greater than between damaged and undamaged conspecific plants (Geervliet et al, 1997), and such differences can be reflected in the attractance of parasitoids to plants (Elzen et al, 1983(Elzen et al, , 1986Fox and Eisenbach, 1992;Geervliet et al, 1996).…”
Section: Introductionmentioning
confidence: 99%